Effects of Aqueous Extract of Vigna unguiculata Seedlings Against Doxorubicin-Induced Cardiotoxicity and Kidney damage In Female Albino Rats - Oseni, Olatunde A.; K. Idowu, Ademola S.; Isah, Aminat (International Journal of Innovative Research in Medical Science, 2016)
Doxorubicin is an anthracycline drug which is believed to cause immediate damage to myocardial cells by free radical generation in the cause of treatment of cancer. This study was however aimed to investigate the effects of the aqueous extract of the seedlings of Vigna unguiculata on heart, kidney as well as lipid profile disorders caused by this drug on female Wistar albino rats. Fifteen female Wistar albino rats were divided into three groups. Group 1 animals served as normal positive control; Group 2 animals served as negative control which were treated with 0.5mL of (20mg/kg body weight doxorubicin) while Group 3 animals were treated with 0.5mL each of 20mg/kg body weight doxorubicin and 10% aqueous extract of seedlings of Vigna unguiculata. Some enzyme markers and lipid contents were determined. The results of the study showed an increase in the activities of plasma ALP and AST after treatment with the drug except in the heart for AST which showed a significant reduction, while treatment with the extract brought about a decrease in the plasma and the organs except for kidney AST. The ALT on the other hand showed slight increase in the plasma with a decrease in the kidney and heart after treatment with the drug as the treatment with the extract tend to restore it to the control in both cases, there was increased plasma and kidney but reduced heart HDL-C after treatment with the drug which was observed to be restored to control after treatment with extract in both situations. The triglyceride and total cholesterol did not show similar trend in the plasma and the studied organs. The LDL-C was also observed to be increased in both plasma and organs after the treatment with the drug which later reduced significantly towards the control after the administration of the sprout extract. The present study has shown that the doxorubicin has damaging effects on both kidney and heart tissues while the sprouts extract produce a restoration to the normal in both organs.